Avaliação da condição de " tão bom quanto novo": uma aplicação envolvendo a manutenção de motores convencionais das aeronaves Universal T-5" - Alexandre Olympio Dower Polezzi (2006)
After a usual preventive maintenance routine it is usually assumed that a system returns to the condition of As Good As New" (AGAN). This work uses some statistical tools to propose a methodology able to test if a system returns to the Condition of AGAN and, in the cases in which the supposition cannot be validated, to determine a coefficient reliable tomeasure the system degradation. A real example related to the Universal aircraft of the Brazilian Air Force illustrates the proposed methodology. The data set considers information from 43 aircrafts. From the data set and the determination of the degradation coefficient it is possible to define Intervals Between Maintenances (TBO's) variables with the number of maintenances that the system has been submitted to, as well as, taking a series of practical conclusions for optimization of the maintenance routines.Keywords: Bootstrap, Maintenance, Time Between Overhaul (TBO), Maximum Likelihood Estimator. etc.